Analysis of Factors Affecting Material Supply Chain Performance in High-Rise Building Construction Projects - Rahayu, Jatiningrum; Putra, I Nyoman Dita Pahang (Jurnal Talenta Sipil, 2025)
The construction industry plays a vital role in the economic development and infrastructure of a country. One of its main challenges lies in the complexity of high-rise building projects, which require tight coordination in the procurement of materials, equipment, and resource management, involving multiple parties that form a complex supply chain. This study aims to analyze the factors that influence the performance of the material supply chain, in order to improve the performance of the material supply chain in the future, with a focus on the flow in the supply chain. The research involved respondents from several high-rise construction projects using purposive sampling techniques. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to identify relationships among variables. The results show that information flow and financial flow have a positive and significant impact on material supply chain performance, whereas material flow does not show a significant effect. However, proper monitoring and management of material flow remain essential to improving supply chain performance.